2014
DOI: 10.1103/physrevd.89.014018
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive gluon production in pion-proton collisions and the principle of maximum conformality renormalization scale

Abstract: The contribution of the higher-twist mechanism to the large-p T inclusive gluon production cross section in πp collisions is calculated in case of the principle of maximum conformality and BrodskyLepage-Mackenzie approaches in the dependence of the pion distribution amplitudes. The highertwist cross sections obtained in the framework of the principle of maximum conformality and Brodsky-Lepage-Mackenzie approaches, and compared and analyzed in relation to the leadingtwist cross sections and each other.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In addition to the examples discussed here, other PMC applications can be found in Refs. [79][80][81][82][83][84]86]. The predicted error bars for "unknown" higher-order corrections under the PMC scale setting quickly approaches a steady point.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the examples discussed here, other PMC applications can be found in Refs. [79][80][81][82][83][84]86]. The predicted error bars for "unknown" higher-order corrections under the PMC scale setting quickly approaches a steady point.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent higher order PMC applications can be found in Refs. [39][40][41][42][43][44][45][46][47][48]. In particular, we have shown that after applying the PMC, the SM predictions for the top-quark charge asymmetry at the Tevatron have only 1σ deviation from the CDF and D0 measurements [19]; the large discrepancies of the top-quark charge asymmetry between the SM estimate and the data are thus greatly reduced.…”
Section: Introductionmentioning
confidence: 85%
“…The calculation and analysis of the higher-twist effects on the dependence of the pion distribution amplitude in inclusive gluon production at πp collision within holhographic and pQCD approaches are the interesting research problems. In our previously study [12], using the principle of maximum conformality (PMC) and Brodsky-Lepage-Mackenzie (BLM) approaches, we have calculated the contribution of the higher-twist mechanism to the largep T inclusive gluon production cross section in πp collisions [12]. In this study, we compute the contribution of the higher-twist effects to an inclusive gluon production cross-section by using various pion distribution amplitudes from holographic and pQCD, and applying the frozen and running coupling [17] constant approaches in order to compute the effects of the infrared renormalons.…”
Section: Introductionmentioning
confidence: 93%
“…The aim of this study is calculation and analysis of the inclusive gluon production in the pion-proton collisions using the frozen and running coupling constant approaches. Using this approaches, the higher twist effects have been already calculated by many authors [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%